A Firing Cannon: Bilateral Lower Limb Ischemia as a Manifestation of Cardiac Myxoma. - Elbayomi, Mohamed; Groß, Raphael; Presheet, Pathare; Agaimy, Abbas; May, Mattias; Wayend, Micheal; Heim, Christian (Thoracic and Cardiovascular Surgeon Reports, 2024)
Background Cardiac myxomas are the most common primary cardiac neoplasms. Case Description We present a case of a middle-aged lady with cardiac myxoma in her left atrium awaiting semi-elective surgery. During the preoperative period, the patient presented emergently with acute bilateral lower limb ischemia. This lady was fortunate to have these emboli fired towards a tissue with ischemia tolerance capacity. If these emboli had been directed toward the central nervous system, this patient would have experienced devastating complications and even death. Conclusion This presentation opens the debate on the timing of surgical intervention in myxoma patients.
EVALuna2:578864